2017
DOI: 10.1186/s40795-017-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

A valid and reliable nutrition knowledge questionnaire for track and field athletes

Abstract: Background: Establishing an understanding of an athlete's nutrition knowledge can inform the coach/practitioner and support the development of the athlete. Thus the purpose of the study was to develop a psychometrically valid and reliable tool to assess general and sport nutrition knowledge. Methods: An 85 question questionnaire was developed in consultation with a panel of experts. Ninety-eight participants from the UK completed the questionnaire, and again 3 weeks later. The participants were classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…These differences in knowledge score were statistically significant for the total questionnaire, but also for both the “General knowledge of nutrition” and “Sports nutrition” sections, thus demonstrating that our questionnaire can discriminate between adolescents with different knowledge levels. Similar to the present findings, in previous studies, people with potential differences in NK (e.g., dietitians versus other workers, students with or without a nutrition background) also showed higher NK compared to non-experts [ 4 , 16 ]. Other studies on sports nutrition evaluated possible differences between groups that received or did not receive nutritional education [ 15 , 16 , 35 , 38 , 50 ] but, in the majority of them, the participants were adults (i.e., college students or athletes) and not adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These differences in knowledge score were statistically significant for the total questionnaire, but also for both the “General knowledge of nutrition” and “Sports nutrition” sections, thus demonstrating that our questionnaire can discriminate between adolescents with different knowledge levels. Similar to the present findings, in previous studies, people with potential differences in NK (e.g., dietitians versus other workers, students with or without a nutrition background) also showed higher NK compared to non-experts [ 4 , 16 ]. Other studies on sports nutrition evaluated possible differences between groups that received or did not receive nutritional education [ 15 , 16 , 35 , 38 , 50 ] but, in the majority of them, the participants were adults (i.e., college students or athletes) and not adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…Comparison with previous questionnaires is tricky because of the differences between present and previously validated tools, for instance, in terms of the number of items, type of questions, and target populations. Among the studies validating questionnaires on general and sports NK, Furber and co-workers developed a 62-item questionnaire in a cohort of UK-based track and field athletes [ 16 ]. The authors compared NK between subjects with nutrition training (i.e., sports nutritionists and dietitians) and those without nutrition training (i.e., professionals and postgraduate students with no exposure to any form of nutrition training).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutrition knowledge questionnaires developed so far have some limitations. Either they are weak in the area of psychometric validation or they target a limited area of nutrition knowledge (1)(2)(3)(4)(5)(6)(7)(8). For example, Towler and Shepherd showed that their questionnaire has good internal reliability and construct validity (9).…”
Section: Introductionmentioning
confidence: 99%